Gugon Tuhon dalam Pageblug di Perkotaan Jawa Periode Kolonial - Adji, Fransisca Tjandrasih; Priyatmoko, Heri; Rooyackers, Max (Balai Pelestarian Kebudayaan Wilayah X, 2023)
Long before Covid-19, in the 19th to early 20th century, pageblug (epidemic) hit the residents of the Vorstenlanden and claimed many lives. This article aims to review the pageblug phenomenon in urban Java during the colonial period using a local history approach. Based on manuscript, archive and mass media data, it is known that Javanese society responded with irrational actions and belief in gugon tuhon (local beliefs) because of the pageblug. In the Western perspective, which prioritized logical thinking, this was seen as unreasonable and even to be considered occult. The results show that there was a relationship between pageblug, jampi (mantra), and gugon tuhon. There had been various efforts to overcome disease or illness using medical and non-medical methods. The method of medical treatment with jampi is recorded in Serat Primbon Mixture of Jampi Jawi and Serat Gugon Tuhon. Because there were rational and irrational thoughts about pageblug, the way jampi was used was also rational and irrational in the view of today’s society. The irrational side was supported by the gugon tuhon which was believed in by the local community.